Granuloma Multiforme: A Rare Granulomatous Disease - Yogesh Poudyal; Anita Shah (Case Reports in Dermatological Medicine)
Granuloma Multiforme (GM) is a reactive skin disorder with annular lesion and focal necrobiosis. It was first described in Nigeria (Africa), since than it was mostly described from various regions of Africa where leprosy was endemic. Outside Africa, this disease is rarely reported. Till 2016 only five cases were reported from India. This is the second case report from Nepal. A fifty-nine-year-old female, farmer by occupation, presented with annular and polycyclic plaques with elevated beaded border for one year. It was distributed over upper trunk, lower back, and arms, and was mildly pruritic. Histopathologically, loss of elastic fibres at focal area of upper dermis, with elastic fibres engulfed histiocytes were noted. GM was mostly noted from leprosy endemic areas of Africa. Clinically, it is very difficult to distinguish from granuloma annulare. This report adds the number of GM occurrence in Asia especially from area where leprosy is still prevalent. This report also emphasizes in resource poor settings where most diagnosis is made clinically, the granuloma annulare should be looked for very carefully in order not to miss GM.